Inovasi Metodologi Pengajaran Di Sekolah Dasar: Strategi Efektif Untuk Meningkatkan Kualitas Pendidikan Guru - Megan Asri Humaira; Effane, Anne; Hasanuddin, Nurqadriyanti (Jurnal Ilmiah Edukatif, 2024)
This research explores teaching methodology innovations in primary schools as an effective strategy to improve the quality of teacher education. Innovations such as project-based approaches, flipped classroom, and digital technology integration are analysed to see their impact on teachers‘ professional development and students’ learning experience. The research method used in this study is the literature review method. The results show that the application of these new methodologies helps teachers deepen their subject matter and pedagogy, and improve their competence and motivation. Continuous support through training and seminars is essential for the successful implementation of this innovation. In addition, the innovative teaching methodology was shown to promote students' engagement and understanding, which in turn improved their academic outcomes and social-emotional skills. The findings confirm the importance of innovative teaching methodologies in creating a dynamic and high-quality learning environment in primary schools.